1998
DOI: 10.1161/01.cir.97.9.857
|View full text |Cite
|
Sign up to set email alerts
|

Abciximab Therapy and Unplanned Coronary Stent Deployment

Abstract: Background-The clinical and angiographic demographics of patients requiring unplanned coronary stent deployment and the optimal adjunct pharmacotherapy in this population are not well described. This report details the EPILOG trial experience with unplanned coronary stent deployment and the effect of abciximab platelet glycoprotein IIb/IIIa blockade to improve clinical outcomes during 6 months of follow-up. Methods and Results-After randomization in the EPILOG double-blind, placebo-controlled trial of abcixima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…That stents improve long-term prognosis, such as preventing restenosis and revascularization, has previously been reported [31]. Still, recent studies have shown that stent implantation is related to more frequent CK elevation than plain balloon PTCA [32]. In this study, in the stent group, CK elevation was the only predictor of revascularization.…”
Section: Discussionsupporting
confidence: 55%
“…That stents improve long-term prognosis, such as preventing restenosis and revascularization, has previously been reported [31]. Still, recent studies have shown that stent implantation is related to more frequent CK elevation than plain balloon PTCA [32]. In this study, in the stent group, CK elevation was the only predictor of revascularization.…”
Section: Discussionsupporting
confidence: 55%
“…Abciximab (ReoPro®) binds to the platelet glycoprotein IIb/IIIa receptor, which is the major platelet surface receptor involved in platelet aggregation. The effect of glycoprotein IIb/IIIa receptor blockade in the prevention of infarcts during coronary intervention is well established in the literature [7,8,9,10,11,12,13]. Current studies investigate the efficacy of glycoprotein IIb/IIIa inhibition in the acute phase of stroke [14].…”
Section: Introductionmentioning
confidence: 99%
“…32,33 As shown in Figure 2, in the Evaluation of PTCA to Improve Long-term Outcome by c7E3 GPIIb/IIIa Receptor Blockade (EPILOG) trial, Ͼ300 patients underwent stenting because of suboptimal balloon angioplasty results, and the benefit for IIb/IIIa inhibition with respect to reduction of MI and emergency revascularization was striking. 32 Of note, the favorable effects for combined IIb/IIIa inhibition (administered on a prophylactic basis) and stenting had thus far been shown only in patients with poor or suboptimal initial results. A dedicated trial (known as Evaluation of Platelet IIb/IIIa Inhibitor for Stenting [EPISTENT]) studied the use of IIb/IIIa blockade with elective stenting.…”
Section: Stents and Iib/iiia Inhibitorsmentioning
confidence: 99%
“…They first ion-implanted the nonradioactive element 31 P beneath the surface of the stent. The stents were then made radioactive by exposure to neutron irradiation, which converts a fraction of the 31 P atoms to 32 P, a pure ␤-particle emitter. This technique results in an even distribution of 32 P within the stent, which ensures homogeneous distribution of ␤-particle irradiation from the stent.…”
Section: Radioactive Stentsmentioning
confidence: 99%
See 1 more Smart Citation